123I-labeled HIV-1 tat peptide radioimmunoconjugates are imported into the nucleus of human breast cancer cells and functionally interact in vitro and in vivo with the cyclin-dependent kinase inhibitor, p21(WAF-1/Cip-1). - Hu, M; Chen, P; Wang, J; Scollard, D; Vallis, K; Reilly, R (2007)
PURPOSE: To evaluate the internalization and nuclear translocation of (123)I-tat-peptide radioimmunoconjugates in MDA-MB-468 breast cancer cells and their ability to interact with the cyclin-dependent kinase inhibitor, p21(WAF-1/Cip-1). METHODS: Peptides [GRKKRRQRRRPPQGYGC] harboring the nuclear-localizing sequence from HIV tat domain were conjugated to anti-p21(WAF-1/Cip-1) antibodies. Immunoreactivity was assessed by Western blot using lysate from MDA-MB-468 cells exposed to EGF to induce p21(WAF-1/Cip-1). Internalization and nuclear translocation were measured. The ability of tat-anti-p21(WAF-1/Cip-1) to block G(1)-S phase arrest in MDA-MB-468 cells caused by EGF-induced p21(WAF-1/Cip-1) was evaluated. Tumor and normal tissue uptake were determined at 48 h p.i. in athymic mice implanted s.c. with MDA-MB-468 xenografts injected intratumorally with EGF. RESULTS: There was 13.4+/-0.2% of radioactivity internalized by MDA-MB-468 cells incubated with (123)I-tat-anti-p21(WAF-1/Cip-1) and 34.6+/-3.1% imported into the nucleus. Tat-anti-p21(WAF-1/Cip-1)(8 muM) decreased the proportion of EGF-treated cells in G(1) phase from 81.9+/-0.7% to 46.1+/-0.7% (p<0.001), almost restoring the G(1) phase fraction to that of unexposed cells (25.8+/-0.2%). Non-specific tat-mouse IgG did not block EGF-induced G(1)-S phase arrest. Tumor uptake of radioactivity was higher in mice injected with EGF to induce p21(WAF-1/Cip-1) than in mice not receiving EGF (3.1+/-0.4% versus 1.8+/-0.2% ID/g; p=0.04). Western blot analysis of tumors revealed a threefold increase in the p21(WAF-1/Cip-1)/beta-actin ratio. CONCLUSION: We conclude that intracellular and nuclear epitopes in cancer cells can be functionally targeted with tat-radioimmunoconjugates to exploit many more epitopes for imaging and radiotherapeutic applications than have previously been accessible.